2002
DOI: 10.1103/physrevb.66.075401
|View full text |Cite
|
Sign up to set email alerts
|

Conductance oscillations in metallic nanocontacts

Abstract: We examine the conductance properties of a chain of Na atoms between two metallic leads in the limit of low bias. Resonant states corresponding to the conductance channel and the local charge neutrality condition cause conductance oscillations as a function of the number of atoms in the chain. Moreover, the geometrical shape of the contact leads influences the conductivity by giving rise to additional oscillations as a function of the lead opening angle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 21 publications
5
54
0
Order By: Relevance
“…A similar effect was found for other monovalent alkali-metal atoms such as Cs, but an opposite behavior, with a conductance bigger for even numbers of atoms than for odd numbers of atoms, was predicted for noble-metals (Cu, Ag and Au) [23]. The even-odd oscillation of the conductance for atomic wires of Na has also been analyzed using a pseudoatom-jellium model [19], where it was found that the sign of the effect is sensitive to the lead cone angle. Applying the first-principle recursion-transfer-matrix method Hirose at al.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…A similar effect was found for other monovalent alkali-metal atoms such as Cs, but an opposite behavior, with a conductance bigger for even numbers of atoms than for odd numbers of atoms, was predicted for noble-metals (Cu, Ag and Au) [23]. The even-odd oscillation of the conductance for atomic wires of Na has also been analyzed using a pseudoatom-jellium model [19], where it was found that the sign of the effect is sensitive to the lead cone angle. Applying the first-principle recursion-transfer-matrix method Hirose at al.…”
supporting
confidence: 57%
“…4, 23 and even for a model in which D = d, this phase is in general, non-zero. Consequently, the even-odd behavior of the conductance strongly depends on the details of the coupling of the chain to the leads (through the phase shift Φ LR ) and this is the reason for the different predictions in the literature [4,10,12,18,19,23]. It is obvious from (1) that the conductance g becomes unity when the two leads are identical (r ′ L = r R ), and the cosine term is 1.…”
mentioning
confidence: 99%
“…44, we do not see a strong lead-shape dependence in the conductance. The widening of the cone angle lowers the conductance as the edges of the wire become sharper.…”
Section: A Atomic Wirementioning
confidence: 82%
“…Here, it should be noted that the deviation of the conductance from the quantized value itself is not surprising. Conductances of atomic chains and atomic point contacts have been found to be sensitive to their structures and interface geometries, as shown by a few theoretical studies [13,14,33] and indicated by the experimental fact that the peaks of the conductance histogram of the atomic point contacts at the quantized values are not very sharp. It is also worth mentioning that dissipation processes in atomic chains, such as the excitation of the atomic vibrations by the electrons traversing the chain [34], have not been considered in our calculation.…”
Section: Effects Of Relaxation On Currentsmentioning
confidence: 97%